ANALISIS MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH KABUPATEN PASURUAN - Meidiati, Rizki Ajeng Fitri; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of work motivation, job satisfaction, and Organizational Citizenship Behavior (OCB) on employee performance, both directly and through the mediating role of OCB at the Regional Financial and Revenue Management Agency (BPKPD) of Pasuruan Regency. The population consists of 100 employees, with a saturated sampling technique (census). Data analysis was conducted using the Partial Least Squares (PLS) approach with the help of SmartPLS 3.0 software. The results indicate that work motivation, job satisfaction, and OCB have a positive and significant effect on employee performance. Furthermore, OCB was found to mediate the influence of work motivation and job satisfaction on performance. Therefore, employees who are motivated and satisfied with their jobs tend to exhibit higher levels of OCB, which ultimately leads to improved performance.